Animales de la granja - Stone, Lynn M. (Vero Beach, Fla. : Rourke Pub., 2002)
Describes some of the animals raised on farms for meat and eggs, milk, and wool.
Includes index.
Keywords: Livestock -- Juvenile literature; Domestic animals -- Juvenile literature; Farms -- Juvenile literature; Ganado -- Literatura juvenil; Animales domésticos -- Literatura juvenil; Granjas -- Literatura juvenil